High expression of phosphorylated focal adhesion kinase predicts a poor prognosis in human colorectal cancer - Yu, Guanyu; Xu, Mengnan; Zhou, Leqi; Zheng, Kuo; Zhu, Xiaoming; Sui, Jinke; Xin, Cheng; Chang, Wenjun; Zhang, Wei; Cao, Fuao (Frontiers in Pharmacology, 2022)
Background: Phosphorylated Focal adhesion kinase (FAK) has been reported to be intimately involved in various malignant tumors. The effect of p-FAK on colorectal cancer (CRC) is still disputable. The purpose of this study is to investigate the role of p-FAK in the prognosis of colorectal cancer. Methods: The clinical significance of p-FAK expression in CRC was evaluated by immunohistochemistry in a large cohort, including carcinoma and para-carcinoma tissues from 908 patients, and normal tissues, adenoma, and metastasis tissues. The correlation between p-FAK expression and CRC occurrence was investigated in tumor and other tissues. Factors contributing to prognosis were evaluated using Kaplan-Meier survival analysis and Cox regression model. Results: p-FAK is apparently overexpressed in CRC and metastasis tissues. Compared with low p-FAK expression, patients with high p-FAK expression had shorter overall survival [hazard ratio (HR), 2.200; 95% confidence interval (CI), 1.265–3.452; p < 0.01] and disease-free survival (HR, 2.004; 95% CI 1.262–3.382; p < 0.01) in multivariate Cox analysis after adjusting other prognostic factors. High p-FAK expression was also related to a worse chemotherapeutic response in patients who achieved adjuvant chemotherapy (p < 0.01). Conclusion: Expression level of p-FAK is an independent risk factor and can serve as a prognostic biomarker for CRC. High p-FAK expression predicts an unfavorable prognosis of CRC as well as poor chemotherapeutic response.